Analisis Tematik Kebahagiaan pada Milenial Kelas Menengah - Harimurti, Albertus (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
This current study aimed to map the experience of happiness among middle-class millennials in Indonesia. Data were collected through the written stories and experiences of 37 subjects aged 19-20 years. Using thematic analysis with constructionist epistemology, this research found four major themes across the stories. Subjects portrayed that happiness is a condition in which the subjects: (1) Enjoy the moment, (2) Subjectively, (3) Support from others, and (4) Self-worth. These findings have implications for research models on happiness that can be directed at welfare issues at various levels, namely individual, interpersonal, organizational, and communal which are interconnected and influence each other.